Expanding horizons in the treatment of mantle cell lymphoma: Ibrutinib a novel BTK-targeting inhibitor - Dhingra, Sameer; Sachdeva, Mamta (International Journal of Basic & Clinical Pharmacology, 2017)
Mantle cell lymphoma (MCL) is a non-Hodgkin lymphoma characterized by involvement of the lymph nodes, spleen, blood, and bone marrow with short remission duration to standard therapies and a median overall survival of 4–5 years. Small molecule inhibitors targeting dysregulated pathways (MAPK/ERK, PI3K/PKB/mTOR, JAK/STAT) have significantly improved clinical outcomes in cancer patients. Recently Bruton’s tyrosine kinase (BTK), a crucial terminal kinase enzyme in the B-cell antigen receptor (BCR) signaling pathway, has emerged as an attractive target for therapeutic intervention in human malignancies and autoimmune disorders. Ibrutinib, a novel first-in-human BTK-inhibitor, has demonstrated clinical effectiveness and tolerability in clinical trials, recently been approved by FDA in the treatment of MCL.